Book Review of "Thinking Collaboratively: Learning in a Community of Inquiry" - Barmby, James (Canadian Journal of Higher Education, 2016)
Book review: Garrison, D.R. (2016). Thinking Collaboratively: Learning in a Community of Inquiry. New York: Routledge. Pages 147. Price: 39.95 USD (paperback). ISBN 978-1-138-82432-4